Fe-decorated hierarchical molybdenum carbide for direct conversion of CO2 into ethylene: Tailoring activity and stability. Issue 50 (August 2021) - Raghav, Himanshu; Siva Kumar Konathala, L.N.; Mishra, Neeraj; Joshi, Bhanu; Goyal, Reena; Agrawal, Ankit; Sarkar, Bipul
Graphical abstract: Highlights: A facile hard templated method is explored for the synthesis of hierarchical β-molybdenum carbide. Iron nanoparticles were decorated over β-Mo2 C through wetness impregnation method. A theoretical loading limit of Fe nanoparticles has been calculated using density functional theory (DFT). Fe-doped β-Mo2 C exhibited highly active in the hydrogenation of CO2 into light olefins. The formation rate of methane and CO found minimum for the Fe(0.5)-Mo2 C catalyst at 300°C and at 400°C, respectively. Abstract: In the past few years, the production of olefins from various resources, particularly from carbon-rich sources, such as crude oil, natural gas, coal, and biomass, has received considerable attention. This study presented the production of light olefins by conducting CO2 hydrogenation through modified Fischer–Tropsch synthesis (M-FTS) by employing a Fe-decorated large surface molybdenum carbide catalyst. A novel strategy was adopted for the synthesis of large surface mesoporous molybdenum carbide by using a hard template. A theoretical loading limit of Fe nanoparticles, calculated using density functional theory, was decorated over β-Mo2 C through simple wetness impregnation. The trans isomers of Fe-doped β-Mo2 C exhibited higher symmetry and were energetically slightly more stable for the hydrogenation of CO2 into light olefins than the cis isomers. Under the optimized condition, Fe(0.5)-Mo2 C showed 7.3% CO2 conversion with 79.4% C2 = olefins.